PERAN GURU DAN KEPALA SEKOLAH DALAM MEWUJUDKAN GERAKAN LITERASI SEKOLAH DI SDN CIMATIS KABUPATEN CIANJUR - Hasanah, Tita; Pramono, Setio (Prodi PGMI IAI Sahid, 2025)
This study aims to analyze the role of teachers and principals in realizing the School Literacy Movement (GLS) at SDN Cimatis, Cianjur Regency. The research method used is qualitative with a case study approach. Informants in this study consisted of principals and teachers. Data collection techniques were carried out through interviews, observations, and documentation, then analyzed using triangulation techniques to ensure the validity of the data. The results of the study showed that teachers play a role in the habit of reading 15 minutes before lessons start, using the reading corner, and collaborating with parents to support literacy at home. Meanwhile, the principal plays a role in socializing GLS, forming a school literacy team, and collaborating with stakeholders to support literacy activities. However, the efforts that have been made have not been optimal due to several obstacles, such as the distance of the school, inadequate facilities and infrastructure, and minimal support from the government and community. Therefore, a more comprehensive strategy is needed to overcome these obstacles in order to increase the effectiveness of GLS at SDN Cimatis.